3.8 Pigment resources report: excavations at Sand, Applecross (Scottish Archaeological Internet Reports, 2009)
One purplish-grey nodule of haematite and one of mudstone with an earthy orange limonite cortex were identified. Although found outside the main midden area, there is no reason to suppose the finds are not Mesolithic.